Counsellor-delivered HIV risk reduction intervention addresses safer sex barriers of people living with HIV in KwaZulu-Natal, South Africa. - Cornman, Deborah H; Christie, Sarah; Shepherd, Lindsay M; MacDonald, Susan; Amico, K Rivet; Smith, Laramie R; Shuper, Paul A; Adelaja, Abidemi; Mahlase, Gethwana; Fröhlich, Janet A; Pillay, Sandy; Lalloo, Umesh G; et al. (Psychology & health, 2011)
This study developed an HIV risk reduction intervention for people living with HIV (PLWH) obtaining care at primary healthcare clinics in KwaZulu-Natal, South Africa by (1) conducting elicitation research to understand the dynamics of risk behaviour among PLWH, (2) modifying an existing HIV risk reduction intervention based on research findings and (3) conducting a pilot study to evaluate feasibility, acceptability and fidelity of the modified intervention implemented by trained lay counsellors at a rural clinic in KwaZulu-Natal. A total of 61 healthcare providers and 77 HIV+ patients from four primary healthcare clinics participated in 14 focus groups and 20 individual interviews to identify informational, motivational and behavioural skills (IMB) factors contributing to PLWH's sexual risk behaviour. Elicitation research findings were incorporated into a revised version of Options for Health, an evidence-based risk reduction intervention for PLWH in clinical care. In a 5-day training, lay counsellors learned strategies to address IMB barriers to safer sex identified in elicitation research. The revised intervention, which was implemented by six counsellors with 39 patients, was feasible to implement, acceptable to patients and counsellors, and implemented with good fidelity. This study makes an important contribution towards development of a theory-based HIV risk reduction intervention for PLWH linking prevention with treatment in South Africa.
Keywords: Adult; Aged; Condoms; Counseling; Feasibility Studies; Female; Focus Groups; HIV Infections; Humans; Male; Middle Aged; Pilot Projects; Risk Reduction Behavior; Safe Sex; South Africa; Young Adult